Analysis of Quercetin Levels in the Ethanol Extract of Curry Leaves (Murraya koenigii L.) as a Potential Animal Feed using High-Performance Liquid Chromatography - Sunaryo Hadi Warsito; Mirni Lamid; Mohammad Anam Al Arif; Widya Paramita Lokapirnasari; Siti Rani Ayuti; Aswin Rafif Khairullah; Mira Delima; Intan Permatasari Hermawan; Rakhi Gangil; Zaheer Ahmad (BIO Integration, 2024)
Background: Curry leaf (Murraya koenigii) is a frequently used medicinal plant. The M. koenigii plant is a type of spice in the Rutaceae family. Curry leaf ethanol extract contains flavonoid compounds. Quercetin is a flavonol compound, a flavonoid derivative that has a 3-hydroxyflavone skeleton. There is a need to analyze the quercetin level in curry leaves utilizing high-performance liquid chromatography (HPLC). Methods: This research was conducted from August to October 2023. A total of 500 g of powdered curry leaves were placed in a maceration vessel. The liquid ethanol extract was mixed with the first re-maceration filtration product. Qualitative analysis was performed by comparing the retention time of the sample solution chromatogram with the reference standard solution of quercetin under identical HPLC conditions. Results: The quantity of curry leave ethanol extract was 52.613 g. Analysis of the curry leaf extract samples revealed that sample 1 had a quercetin level of 0.080 mg/g, while sample 2 had a quercetin level of 0.079 mg/g. The final analysis of the curry leaf ethanol extract samples showed an average quercetin level of 0.03%. Conclusion: These results indicate that the curry leave ethanol extract contains flavonoid compounds, especially quercetin.